2012
DOI: 10.1530/erc-11-0367
|View full text |Cite
|
Sign up to set email alerts
|

Pasireotide (SOM230) shows efficacy and tolerability in the treatment of patients with advanced neuroendocrine tumors refractory or resistant to octreotide LAR: results from a phase II study

Abstract: Pasireotide (SOM230) is a novel multireceptor-targeted somatostatin (sst) analog with high binding affinity for sst receptor subtype 1, 2, 3 (sst 1,2,3 ) and sst 5 . Because of this binding profile, pasireotide may offer symptom control in patients with neuroendocrine tumors (NETs) and carcinoid syndrome no longer responsive to octreotide LAR. This was a phase II, open-label, multicenter study of pasireotide in patients with advanced NET whose symptoms of carcinoid syndrome (diarrhea/flushing) were inadequatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
116
1
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 176 publications
(127 citation statements)
references
References 19 publications
7
116
1
3
Order By: Relevance
“…Together, these data raise the question of its use in GEP-NETs. In a phase II clinical trial, pasireotide has been shown to control symptoms related to carcinoid syndrome in 27% of patients with NETs who were resistant to octreotide (Kvols et al 2012). However, the effects of pasireotide in comparison to octreotide on tumor secretion and proliferation and its relationship to WHO grades, sst expression profile, and sst trafficking in GEP-NETs remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…Together, these data raise the question of its use in GEP-NETs. In a phase II clinical trial, pasireotide has been shown to control symptoms related to carcinoid syndrome in 27% of patients with NETs who were resistant to octreotide (Kvols et al 2012). However, the effects of pasireotide in comparison to octreotide on tumor secretion and proliferation and its relationship to WHO grades, sst expression profile, and sst trafficking in GEP-NETs remain to be explored.…”
Section: Introductionmentioning
confidence: 99%
“…When no symptomatic control is achieved, another option of treatment would be the novel multireceptor-targeted somatostatin analogue pasireotide (previously known as SOM230). In a recently published phase II, open-label, multicentre study of pasireotide in patients with advanced NET whose symptoms of carcinoid syndrome (diarrhoea/flushing) were inadequately controlled by octreotide LAR, pasireotide 600-900 μg given subcutaneously reduced daily flushing episodes from 4.9 ± 4.1 at baseline to 1.0 ± 0.8 post-treatment and was effective in controlling the symptoms of diarrhoea and flushing in 27% of patients with advanced NETs who were no longer responsive to octreotide LAR (54). The use of octreotide before invasive procedures is also important to prevent a carcinoid crisis.…”
Section: Carcinoid Syndromementioning
confidence: 97%
“…The search uncovered eleven relevant randomized prospective studies [9][10][11][12][13][14][15][16][17][18][19] , sixteen nonrandomized prospective studies [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] , and thirteen retrospective studies [36][37][38][39][40][41][42][43][44][45][46][47][48] . Where multiple reports and abstracts were published for a single trial or study, only the most recent full publication was included, unless other reports contained data that were not available in the most recent publication.…”
Section: Primary Literaturementioning
confidence: 99%